The Influence of Peer Education on Tooth-brushing Behavior in Islamic Environments - Kartono, Faradhillah; Uly, Nilawati; A, Ridwan; Aswan (Palita: Journal of Social Religion Research, 2025)
Oral health is a vital component of a child's overall quality of life. The 2018 Indonesian Basic Health Research (Riskesdas) revealed that the prevalence of dental caries exceeded 88%. In Luwu Regency, caries rates among schoolchildren remain high. This study aims to analyze the impact of peer education on tooth-brushing behavior among students of Madrasah Ibtidaiyah (MI) 11 Bonelemo, Bajo Barat, Luwu. The research employed a quantitative experimental approach, with 38 students from grades 3–5 serving as participants, divided into two groups: treatment and control. Class leaders were trained as peer educators to deliver tooth-brushing education grounded in the Health Promotion Model (HPM). The results showed significant improvements in tooth-brushing frequency and quality in the treatment group compared with the control group (p<0.05). It confirms the effectiveness of peer education in encouraging children's health behaviors. In the madrasah context, this approach aligns with Islamic values that emphasize cleanliness, as reflected in the saying of the Prophet Muhammad SAW: "Cleanliness is part of faith."